2004
DOI: 10.1002/polb.20333
|View full text |Cite
|
Sign up to set email alerts
|

B. J. Ash, R. W. Siegel and L. S. Schadler, 'Glass‐transition temperature behavior of alumina/PMMA nanocomposites', Journal of Polymer Science Part B: Polymer Physics (2004) 42(23) 4371–4383

Abstract: Alumina/poly(methyl methacrylate) (PMMA) nanocomposites were synthesized by an in situ free-radical polymerization process with 38 and 17 nm diameter ␥-alumina nanoparticles. At extremely low filler weight fractions (Ͻ1.0 wt % of 38 nm fillers or Ͻ0.5 wt % of 17 nm fillers) the glass-transition temperature (T g ) of the nanocomposites drops by 25°C when compared to the neat polymer. Further additions of filler (up to 10 wt %) do not lead to additional T g reductions. The thermal behavior is shown to vary with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
163
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(180 citation statements)
references
References 0 publications
15
163
2
Order By: Relevance
“…Review of the nanocomposite literature provides many similar instances in which modulus changes but T g does not or the direction or relative magnitude of the changes are not the same 35,48,51,67,68 . However, it is also fair to say that this discrepancy has not yet been well studied and is still a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Review of the nanocomposite literature provides many similar instances in which modulus changes but T g does not or the direction or relative magnitude of the changes are not the same 35,48,51,67,68 . However, it is also fair to say that this discrepancy has not yet been well studied and is still a subject of debate.…”
Section: Discussionmentioning
confidence: 99%
“…Basic percolation theory demonstrates that elongated filler particles such as fiber or plate forms can be very effective at forming percolating network at very low volume fractions. 14,18,30,67,68 In addition, the worm-like structure of EG with interconnection between the platelets may add to its enhanced conductivity over ARG as a filler. However, the decreased improvement in conductivity at 5 wt % for ARG and EG samples may indicate occurrence of some particle clustering with increased loading in these systems, which is also consistent with the T g , image analysis, and stiffness data.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in T g have been observed in other confined systems, such as thin films and polymer nanocomposites with nonwetting interfaces, for which the area of the interfacial region is very large. Ash et al 14,15 showed a dramatic decrease in T g in alumina-filled poly(methyl methacrylate) nanocomposites. It was suggested that the nonwetting interfacial region surrounding the nanoparticles (which exhibits enhanced polymer chain mobility compared with the bulk polymer) leads to the change in T g .…”
Section: T Gmentioning
confidence: 99%
“…[12][13][14][15][16][17] Both the sign and magnitude of the shift in T g have been found to be influenced by the interaction between the filler and the polymer matrix. [14][15][16][17] It has been suggested that the glass transition phenomenon observed in confined systems is due to the effects of the interfacial region. Many researchers have reported enhanced polymer chain mobility near a free surface.…”
Section: Introductionmentioning
confidence: 99%
“…In general, however, it seems that a strong interaction between the polymer and the surface tends to increase the glass transition temperature. Likewise, for polymer nanocomposites their glass transition temperatures has been observed to increase, 14 decrease, 15 disappear, 14 or remain unaltered. 16 Although the effects of physical size, confinement, and incorporation of fillers on glass transition temperature have received major attention, physical ageing of these materials has not received adequate investigation.…”
Section: Introductionmentioning
confidence: 99%